2015
DOI: 10.1136/jclinpath-2014-202728
|View full text |Cite
|
Sign up to set email alerts
|

Proteins of the mitotic checkpoint and spindle are related to chromosomal instability and unfavourable prognosis in patients with myelodysplastic syndrome

Abstract: To the best of our knowledge, this is the first report to demonstrate that these proteins are associated with chromosomal abnormalities and poor prognosis in patients with MDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
15
0
1
Order By: Relevance
“…Inversely, there is a correlation between age and expression of the checkpoint genes Mad2, Aurora B and Cdc20 in myelodysplastic syndrome (MDS), an characteristic aging-associated dysplasia of the blood-forming system. The same study also demonstrated a correlation of expression levels of these genes and the developmental stage of MDS, as already discussed in the previous paragraph [ 45 ].…”
Section: Changes Of Mitotic Checkpoint Signaling During the Aging Prosupporting
confidence: 76%
See 2 more Smart Citations
“…Inversely, there is a correlation between age and expression of the checkpoint genes Mad2, Aurora B and Cdc20 in myelodysplastic syndrome (MDS), an characteristic aging-associated dysplasia of the blood-forming system. The same study also demonstrated a correlation of expression levels of these genes and the developmental stage of MDS, as already discussed in the previous paragraph [ 45 ].…”
Section: Changes Of Mitotic Checkpoint Signaling During the Aging Prosupporting
confidence: 76%
“…Further on, expression levels of the SAC components Aurora A/B have been reported for AML cells [ 43 ], whereas upregulation of Aurora A has also been connected to the initiation of myelodysplastic syndrome (MDS) [ 44 ]. This heterogeneous class of various blood cancers also in most cases emerges from transformed HSPCs [ 45 , 46 ]. The van Deursen laboratory showed that overexpression of the MCC regulator Bub1 in mice induced tumor formation [ 47 ], while the level of expression of the gene was reduced in AML specimens and cell lines, such as K562 and HL60 [ 48 , 49 ].…”
Section: Changes In Sac Signaling In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Among these 5 hub genes, MAD2L1 and FANCD2 are associated with ovarian cancer. As a component of the mitotic checkpoint, high levels of MAD2L1 are related to increased cellular proliferation, migration, and metastasis, which can lead to shorter survival in various cancers [22][23][24][25][26]. However, in ovarian cancer, the role of MAD2L1 did not agree with previous findings that patients with lower MAD2L1 levels were less sensitive to paclitaxel and had shorter progression-free survival (PFS) and overall survival (OS) [27,28].…”
Section: Discussionmentioning
confidence: 82%
“…Similarly in breast cancer, where p53 and BRCA1 are also regularly mutated, high MAD2 levels are associated with improved breast cancer specific survival [ 53 ]. Additionally, high grade serous ovarian cancers express lower levels of E-cadherin and higher levels of N-cadherin compared to mucinous which is suggestive of a more epithelial-mesenchymal transition phenotype which in-turn triggers tumour metastasis and possibly reduce the requirement of MAD2 for tumour spread [ 54 , 55 ]. However, due to the limited number of studies on MAD2 expression in ovarian cancer, we cannot conclude if different ovarian subtypes have different survival rates depending on MAD2 expression.…”
Section: Discussionmentioning
confidence: 99%